TANGGUNG JAWAB NEGARA DALAM MENGATASI PERUBAHAN IKLIM GLOBAL BERDASARKAN PRINSIP COMMON BUT DIFFERENTIATED RESPONSIBILITIES DALAM HUKUM INTERNASIONAL - Fikri Ardiyansyah (Jurnal Humaniora & Sosial Sains, 2026)
Global climate change constitutes a multidimensional challenge that requires a collective response from the international community through the framework of international law. This study aims to analyze state responsibility in addressing climate change based on the principle of Common but Differentiated Responsibilities (CBDR) in international law. The research employs a normative legal method using statutory, conceptual, and analytical approaches toward the principal international legal instruments, namely the United Nations Framework Convention on Climate Change, the Kyoto Protocol, and the Paris Agreement. The findings indicate that the CBDR principle serves as the normative foundation of the international climate regime by emphasizing common responsibility among all states while differentiating obligations based on historical emissions and respective national capabilities. The principle has evolved from a strict differentiation model under the Kyoto Protocol to a more universal and participatory approach under the Paris Agreement. Although CBDR provides a framework for global climate justice, its implementation continues to face challenges related to climate finance, technology transfer, and compliance mechanisms. Strengthening accountability and enhancing national ambition are therefore essential to ensure the effective fulfillment of state responsibility in confronting the global climate crisis.